2011
DOI: 10.5483/bmbrep.2011.44.4.267
|View full text |Cite
|
Sign up to set email alerts
|

ZAS3 promotes TNFα-induced apoptosis by blocking NFκB-activated expression of the anti-apoptotic genes TRAF1 and TRAF2

Abstract: ZAS3 is a large zinc finger transcription repressor that binds the κB-motif via two signature domains of ZASN and ZASC. A loss-of-function study showed that lack of ZAS3 protein induced accelerated cell proliferation and tumorigenesis. Conversely, gain-of-function studies showed that ZAS3 repressed NFκB-activated transcription by competing with NFκB for the κB-motif. Based on these observations, we hypothesize that ZAS3 promotes apoptosis by interrupting anti-apoptotic activity of NFκB. Here, we present eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is suggested that the TRAF‐2‐binding BIR1 domain of cIAP2/MALT1 fusion protein is critical for activating NF‐κB and the domain can increase the expression of the NF‐κB target gene, including TRAF‐1 . ZAS3 can repress the TRAF‐1 and TRAF‐2 gene expression and then suppress the NF‐κB anti‐apoptotic process …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the TRAF‐2‐binding BIR1 domain of cIAP2/MALT1 fusion protein is critical for activating NF‐κB and the domain can increase the expression of the NF‐κB target gene, including TRAF‐1 . ZAS3 can repress the TRAF‐1 and TRAF‐2 gene expression and then suppress the NF‐κB anti‐apoptotic process …”
Section: Discussionmentioning
confidence: 99%
“…21 ZAS3 can repress the TRAF-1 and TRAF-2 gene expression and then suppress the NF-kB anti-apoptotic process. 27 T cells play crucial roles in the development of IBD but the relationship between the activity of T cells and the TRAF family is not quite clear. Resent researches have shown that both TRAF-1 and TRAF-2 are required in the T cell response to 4-1BB signaling, and 4-1BB recruits TRAF-1 and TRAF-2 to mediate survival signaling in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a pro-inflammatory cytokine secreted by macrophages and TNF-α exerts a suppressive effect on tumors (16). However, tumors can become TNF-α resistant and eventually most malignant tumors become TNF-α resistant (17,18). For these reasons, many malignant tumors can escape from TNF-α-induced cell death (17).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genes have been shown to be closely involved in apoptotic and proliferative cellular processes, which is interesting given the established links between apoptosis, vascular calcification and CVD 10 12 , 29 , 30 . HIVEP3 31 , EID2 32 , ETS1 33 , MRFAP1 34 , ZNF224 35 , BCL11B 36 , 37 , SKI 38 , 39 , ZMIZ1 40 , GFI1 41 , HDAC4 42 , MAD1L1 43 , NCOR2 44 , 45 , ANKRD11 46 , BANP 47 , and ARID3A 48 , 49 all have functions related to apoptosis, cell survival or cell cycle progression. This highlights the importance of cell cycle activity, apoptosis, and cellular senescence in CKD.…”
Section: Discussionmentioning
confidence: 99%